Remembering the Peruvian Public Health Society: 1950-1968 - Bustíos Romaní, Carlos M. (2021)
A critical review is made of the information available on the Peruvian Public Health Society (SPSP), inaugurated as a scientific-union organization in August 1950, and deactivated at the end of 1968 by a de facto government. With this review, 53 years after this deactivation occurred, we want to keep alive the memory of his efforts for doctrinal unification and technical modernization of Peruvian public health in a difficult context; as well as paying posthumous tribute to his associates, who taught us - with deeds rather than words - what should be the conduct of a Peruvian sanitarian.